Assessment of Body Composition, Lower Limbs Power, and Anaerobic Power of Senior Soccer Players in Portugal: Differences According to the Competitive Level - Tereso, Diogo (2021)
Background. During a soccer game, the most diversified stimuli occur all the time, the physical condition level plays a determinant role, and there may be variations according to the com petitive level. In this sense, the present study aimed to verify differences in body composition, lower limbs power, and anaerobic power, comparing senior soccer players of different competitive levels. Methods. Participants were 81 players belonging to six soccer teams, aged between 18 and 35 years, with a mean age of 23.14 ± 4.23 years, who were divided into three distinct competitive levels: Elite, Sub-Elite and Non-Elite. The players performed bioimpedance evaluations on a tetrapolarInbody270 scale (body composition), the Countermovement Jump (CMJ) through the ChronoJump (lower limbs power), and Running Anaerobic Sprint Test (RAST) (anaerobic power). Results. Based on the com petitive level analysis, we verified that the players present body composition values similar to each other regardless of the competitive level in which they play. Concerning the performance evaluations, we verified that the elite players present higher values of highest jump (p = 0.012; d = 0.76, moderate; and p = 0.022; d = 0.71, moderate) and maximum force produced (p = 0.05; d = 0.64, moderate; and p = 0.002; d = 1.00, moderate), together with higher values of anaerobic power (p < 0.001; d = 2.43, very large; and p < 0.001; d = 2.22, very large), compared to the others. Conclusions. We can thus conclude that there is a homogeneity regarding the body composition of soccer players, regardless of their competitive level; in turn, elite players show better performance indicators in all variables.